Systematic Screening for SARS-CoV-2 to Detect Asymptomatic Infections: An Epitome of Taiwan’s Outbreak - Chih-Chien Cheng; Chia-Chen Liu; Ju-Chuan Yen; Ting-Fang Chiu; Yi-Ning Liu; Thomas Y. Hsueh; Sheng-Huang Hsiao (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Increased studies have revealed that asymptomatic carriers substantially impact the epidemic and that asymptomatic transmission is very common. Therefore, the asymptomatic transmission threat to the spread of the pandemic should not be neglected. Methods. The local outbreak in Taiwan, especially in Taipei City, is unprecedented and paramount and has claimed hundreds of lives, tens of thousands of cases, and enormous economic costs. As care providers and gatekeepers of infectious diseases, Taipei City Hospital has to perform regular polymerase chain reaction (PCR) results of admitted patients and healthcare workers (HCWs) to achieve these goals. Results. In this study, the results revealed a low positive rate of less than 1%, but the asymptomatic proportions could range from 42% to 46%, which bolsters that systematic screening was effective in controlling coronavirus disease-19 (COVID-19) of Novel Coronavirus or Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) and might be an exemplar to other similar scenarios. Universal screening of admitted patients may be important and necessary, especially in asymptomatic patients. Conclusions. Regular screening for healthcare providers is also important during this pandemic, and it is recommended that admitted patients and healthcare providers undergo systemic PCR testing.